Practising Hope through Slam Poetry - Trueman, Nicolette; Beban, Alice; Heather Meikle; Tie, Warwick; Wynyard, Matthew (New Zealand Sociology, 2024)
Nicolette Trueman, Alice Beban, Heather Meikle, Warwick Tie and Matt Wynyard with Lucca Jordan, Gauri Ramesh, Klara Van Den Berg, Abby Bleakley, Oscar Wright, Daniel O’Sullivan, Manit Desai, Elise Fouhy, Kuravainga Ngataa, Kaela Alderson, Shuhan Cao, Elysse Brandon, Connor Menthony, Nao Matsuda, Ava Gilbert, Sajani Dissanayake, Scarlett Baker, Maitê Abrieu, Alicia Kovacs, Thu Mai, Grace Beissel, Angela Du, Shuhan Cao, Sajani Dissanayake, Max Skates, Stellan Port, Angela Yamamoto, Jerry Tran, and Francesca Haddon